RISKS FLOWING FROM THE INTERNET IN THE PARENT'S EYES - BUŁKA, Beata; Justyna, KOŚ (Trends in education, 2009)
This article presents the results of research on the risks flowing from the Internet in the parents' eyes. The research were conducted among a representative group of parents from students Zespół Szkół Ogólnokształcących in Chałupki and Zespół Szkół Ekonomicznych in Wodzisław Śląski.
Keywords: Internet; parents; students.